2010
DOI: 10.1016/j.cell.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Polysaccharide Use in Intestinal Bacteroides Species Determines Diet-Induced Microbiota Alterations

Abstract: Summary The intestinal microbiota impacts many facets of human health and is associated with human diseases. Diet impacts microbiota composition, yet mechanisms that link dietary changes to microbiota alterations remain ill-defined. Here we elucidate the basis of Bacteroides proliferation in response to fructans, a class of fructose-based dietary polysaccharides. Structural and genetic analysis disclosed a fructose-binding, hybrid-two-component signaling sensor that controls the fructan utilization locus in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
672
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 625 publications
(722 citation statements)
references
References 41 publications
22
672
3
5
Order By: Relevance
“…BT was chosen based on its status as a common and abundant member of the human microbiota that has been extensively characterised (Hooper et al, 2000;Martens et al, 2008;Mahowald et al, 2009;Sonnenburg et al, 2010). We analyzed the luminal contents of five GI regions dissected from each experimental animal: (1) stomach, (2) jejunum, (3) ileum, (4) cecum and (5) proximal colon.…”
Section: Resultsmentioning
confidence: 99%
“…BT was chosen based on its status as a common and abundant member of the human microbiota that has been extensively characterised (Hooper et al, 2000;Martens et al, 2008;Mahowald et al, 2009;Sonnenburg et al, 2010). We analyzed the luminal contents of five GI regions dissected from each experimental animal: (1) stomach, (2) jejunum, (3) ileum, (4) cecum and (5) proximal colon.…”
Section: Resultsmentioning
confidence: 99%
“…Mice GF Swiss-Webster (SW) and C57BL/6J and conventional (RF, Taconic Inc., Cambridge city, IN, USA) SW mice were maintained as previously described (Sonnenburg et al, 2010). Humanization was performed using human fecal samples obtained from healthy anonymous donors.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen feces were thawed by dilution in an equal volume of prereduced phosphate-buffered saline in anerobic conditions and 0.2 ml non-settling material was gavaged into GF-recipient mice. Mice were fed standard diet (Purina LabDiet 5K67) or polysaccharide-deficient diet (Bio-Serv, Frenchtown, NJ, USA; Sonnenburg et al, 2010). GF mice were mono-or bi-associated using oral gavage with 10 8 colony-forming units of Bacteroides thetaiotaomicron (Bt) VPI-5482 and/or Bifidobacterium longum (Bl) NCC2705.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomic studies and experiments with isolated strains revealed that members of the genus Bacteroides are broadly adapted to the degradation of host glycans and terrestrial plant material (2). This adaptation is exemplified by the enzyme systems devoted to starch, pectin, hemicelluloses, and other plant carbohydrates as well as host glycans (2,3); the wide variety of genes encoding enzymes for the degradation of these carbohydrates dominate carbohydrate active enzyme, or CAZyme, arsenals in human gut metagenome datasets. Hence, the evolution of this carbohydrate catabolizing machinery is key for host and microbiome mutualism.…”
mentioning
confidence: 99%